Ex vivo anti-malarial drug susceptibility of Plasmodium falciparum isolates from pregnant women in an area of highly seasonal transmission in Burkina Faso - Tahita, Marc C (Malar J, 2015)
BACKGROUND: Ex vivo assays are usually carried out on parasite isolates collected from patients with uncomplicated Plasmodium falciparum malaria, from which pregnant women are usually excluded as they are often asymptomatic and with relatively low parasite densities. Nevertheless, P. falciparum parasites infecting pregnant women selectively sequester in the placenta and may have a different drug sensitivity profile compared to those infecting other patients. The drug sensitivity profile of P. falciparum isolates from infected pregnant women recruited in a treatment efficacy trial conducted in Burkina Faso was determined in an ex vivo study. METHODS: The study was conducted between October 2010 and December 2012. Plasmodium falciparum isolates were collected before treatment and at the time of any recurrent infection whose parasite density was at least 100/µl. A histidine-rich protein-2 assay was used to assess their susceptibility to a panel of seven anti-malarial drugs. The concentration of anti-malarial drug inhibiting 50% of the parasite maturation to schizonts (IC(50)) for each drug was determined with the IC Estimator version 1.2. RESULTS: The prevalence of resistant isolates was 23.5% for chloroquine, 9.2% for mefloquine, 8.0% for monodesethylamodiaquine, and 4.4% for quinine. Dihydroartemisinin, mefloquine, lumefantrine, and monodesethylamodiaquine had the lowest mean IC(50) ranging between 1.1 and 1.5 nM respectively. The geometric mean IC(50) of the tested drugs did not differ between chloroquine-sensitive and resistant parasites, with the exception of quinine, for which the IC(50) was higher for chloroquine-resistant isolates. The pairwise comparison between the IC(50) of the tested drugs showed a positive and significant correlation between dihydroartemisinin and both mefloquine and chloroquine, between chloroquine and lumefantrine and between monodesethylamodiaquine and mefloquine. CONCLUSION: These ex vivo results suggest that treatment with the currently available artemisinin-based combinations is efficacious for the treatment of malaria in pregnancy in Burkina Faso. TRIAL REGISTRATION: ClinicalTrials.gov ID: NCT00852423 ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12936-015-0769-1) contains supplementary material, which is available to authorized users.